2023
DOI: 10.1002/tox.23745
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor SNRPA associated with microvascular invasion promotes hepatocellular carcinoma metastasis through activating NOTCH1/Snail pathway and is mediated by circSEC62/miR‐625‐5p axis

Abstract: Microvascular invasion (MVI) is a crucial risk factor related to the metastasis of hepatocellular carcinoma (HCC), but the underlying mechanisms remain to be revealed. Characterizing the inherent mechanisms of MVI may aid in the development of effective treatment strategies to improve the prognosis of HCC patients with metastasis. Through the Gene Expression Omnibus (GEO) database, we identified that small nuclear ribonucleoprotein polypeptide A (SNRPA) was related to MVI in HCC. SNRPA was overexpressed in MVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Paraffin blocks of PTC and normal tissue were deparaffinized and hydrated, followed by treatment with citrate buffer as previously described 40 . Sections were treated with Anti‐SYK antibody (1:200, ab155187, Abcam, USA), anti‐p‐SYK (1:200, ab62338, Abcam, USA), and anti‐Galectin‐3 (1:150, ab2785, Abcam, USA) for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paraffin blocks of PTC and normal tissue were deparaffinized and hydrated, followed by treatment with citrate buffer as previously described 40 . Sections were treated with Anti‐SYK antibody (1:200, ab155187, Abcam, USA), anti‐p‐SYK (1:200, ab62338, Abcam, USA), and anti‐Galectin‐3 (1:150, ab2785, Abcam, USA) for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Paraffin blocks of PTC and normal tissue were deparaffinized and hydrated, followed by treatment with citrate buffer as previously described. 40 Sections were treated with Anti-SYK antibody (1:200, ab155187, Abcam, USA), anti-p-SYK (1:200, ab62338, Abcam, USA), and anti-Galectin-3 (1:150, ab2785, Abcam, USA) for 1 h at 37 C. Secondary antibody was added for 30 min incubation, followed by DAB staining for protein signal detection. IHC scores were computed by multiplying staining intensity (negative, 0; weak, 1; moderate, 2; or strong, 3) and percentage of positive cells (0; <25%, 1; 25%-50%, 2; 50%-75%, 3; >75%, 4;).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…4 For instance, circSEC62 promoted SNRPA levels by silencing miR-625-5p and affected HCC microvascular invasion. 10 Since ROBO1 was aberrant expressed in various cancers, [11][12][13] but the function of ROBO1 derived circRNAs in cancers still remained unclear. Among 40 circRNAs derived from parental gene ROBO1, only hsa_circ_0124696 (back splicing exon 5-8 of ROBO1) was identified to regulate the liver metastasis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are derived from a non‐canonical form of variable splicing, where the splice donor spot of one exon is ligated to the splice acceptor spot of an up stream exon 11 . Diverse from linearity RNA, circRNAs produce a continuous steady loop framework in the absence of 5′cap or 3′tail, which promotes its resistant feature to exonuclease digestion 12 . The biofunction of circRNAs is versatile, changing greatly from the location, binding spots and behavior patterns of circRNAs 13 .…”
Section: Introductionmentioning
confidence: 99%
“…absence of 5 0 cap or 3 0 tail, which promotes its resistant feature to exonuclease digestion. 12 The biofunction of circRNAs is versatile, changing greatly from the location, binding spots and behavior patterns of circRNAs. 13 Andreeva 14 reported that circRNAs existed extensively in cellular tissue of plants and animals.…”
Section: Introductionmentioning
confidence: 99%